2003
DOI: 10.4278/0890-1171-17.6.382
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Hardiness, Supervisor Support, Group Cohesion, and Job Stress as Predictors of Job Satisfaction

Abstract: Implications for targeted worksite health promotion efforts to lower job stress and enhance job satisfaction are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 46 publications
(82 reference statements)
6
61
0
12
Order By: Relevance
“…The body mass index (BMI) of the subjects were calculated as body weight (kg) / (body height (m)) 2 . Blood samples were collected after at least 12 h of nocturnal fasting.…”
Section: Measurement Of Anthropometries and Plasma Biochemical Paramementioning
confidence: 99%
See 1 more Smart Citation
“…The body mass index (BMI) of the subjects were calculated as body weight (kg) / (body height (m)) 2 . Blood samples were collected after at least 12 h of nocturnal fasting.…”
Section: Measurement Of Anthropometries and Plasma Biochemical Paramementioning
confidence: 99%
“…In a work setting these health indicators may be evaluated quantitatively by indices of absenteeism, job satisfaction, and work stability." 1) Job satisfaction is defined as a pleasurable or positive emotional state resulting from the appraisal of one's job experiences as fulfilling important job values 2) . Since job satisfaction has been related to absenteeism 3) , job stress 4) , and quality of life 5) , it is important for occupational health to justify the impact of health promotion programs on job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Mcclenahan et al (35) concluded that high demands and low control and low support accounted for 26%, 6%, and 8% of the variance in job satisfaction, psychological distress and burnout, respectively. Lack of support and poor communication may act as stressors, therefore leading to the perception of work stress (36). Providing essential information and skills about mental health, including occupational stressors, have an impact on the mental health of employees, at least in the short term (37).…”
Section: Discussionmentioning
confidence: 99%
“…Job satisfaction is defined as a pleasurable or positive emotional state resulting from appraisal of one's job experiences as fulfilling important job values 1) . Since the level of job satisfaction has been related to absenteeism, job stress and quality of life, it is important for occupational health to justify the impact of health promotion programs on job satisfaction 2,3) .…”
Section: Introductionmentioning
confidence: 99%